MODERN TENDENCIES OF THE “COMPLIANCE-CONTROL” SYSTEM AGAINST CORRUPTION IN THE PRIVATE SECTOR ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
The fact that the scale of corruption-related crimes in the world is increasing year by year indicates that it is necessary to improve the organizational and legal foundations of the "compliance-control" system in this field. According to the analysis, the global damage of corruption is about 3 trillion US dollars, of which about 1 trillion US dollars is caused by giving and receiving bribes. At the global level, up to 25% of public procurement funds are lost due to corruption. On the other hand, the fact that this number is 5% of the world's gross domestic product indicates that the fight against corruption remains in a negative state. In Uzbekistan, consistent measures are being taken to introduce a system based on advanced international standards for the prevention of corruption and an uncompromising fight against it. At this point, the introduction of "compliance-control" structures as one of the systems that have a positive effect in preventing corruption risks among all state bodies and organizations is of particular importance.